Influência das propriedades físicas de graviola e aditivos na secagem em leito de jorro com alimentação intermitente - Dantas, Thayse Naianne Pires (2018)
The objective of this work was to analyze the influence of physical properties of formulated mixtures of soursop pulp with milk or albumin and the operating conditions, concentration and temperature, on the definition of mathematical equations describing the phenomena of spouted bed drying. Macroscopic heat and mass balances were written, describing the powder production and the drying behavior of soursop pulp/milk or soursop pulp/albumin in spouted bed with intermittent feeding and high-density polyethylene or polypropylene as inert particles. The drying tests were carried out following 2² factorial plannings with 3 repetitions at the central point. The following independent variables were considered: inlet air temperature (60 - 80ºC) and milk or albumin concentrations (30 - 50%). From the physical properties of the mixtures, the models that represent the flow of powder as function of time were determined. Considering suspension accumulation inside the device, a model was developed to evaluate the temperature of the air at the dryer outlet. The results obtained with mathematical modelling were compared with experimental data, indicating that the model fits the process well, and gives reasonable values for outlet air temperature and mass of powder recovered.